Ocean-atmosphere coupled modes of decadal variability in the Southern Hemisphere - Wang, Gang (Monash University. Faculty of Science. School of Earth, Atmosphere and Environment, 2015)
The Southern Ocean has a critical influence on the global climate, and any long-term variability in the Southern Ocean can have both regional and global impacts significantly. However, sparse observations limit the study of the long-term variation. To test the quality of models simulating the natural sea surface temperature (SST) variability, the SST variability in the global oceans is evaluated in simulations of the Climate Model Intercomparison Project Phase 3 (CMIP3) and CMIP5 models. The result shows that some models demonstrate good skill in simulating the observed spatial structure of the SST variability in the tropical domains and less so in the extra-tropical domains. The CMIP5 ensemble exhibits some improvement over the CMIP3 ensemble, mostly in the tropical domains on SST variability simulation. Further, the spatial structure of the SST modes of the CMIP3 and CMIP5 super ensemble is more realistic than any single model, which is mostly used for the following study. Several SST leading modes in the Southern Ocean are discussed on decadal and even larger time scales using CMIP5 data set based on EOF analysis. We compare the modes against several simple null hypotheses, such as isotropic diffusion (red noise) and a Slab Ocean model, to investigate the sources of decadal variability and the factors affecting the propagation and decay of long-term anomalies. The result reveals that the annular mode with largest amplitudes in the Pacific, the basin-wide monopole mode and South Pacific dipole are the principle patterns with low-frequency variability, which contain the dual effects of internal intrinsic processes as well as external forcing and teleconnections. The annular mode is mostly affected by El Niño Southern Oscillation (ENSO) via teleconnection especially in the South Pacific domain and by local Southern Annular Mode (SAM) over the whole Southern Ocean. The monopole mode and South Pacific dipole mode, while they both demonstrate pronounced multi-decadal and longer time scales variability, are firstly inducted by the Wave-3 patterns in the atmosphere and further developed via ocean dynamics. The causes and characteristics of interannual-decadal SST variability in the Southern Ocean are further investigated with an ocean general circulation model and a simplified band ocean model. Possible factors are examined affecting the generation, propagation and decay of long-term anomalies with a series of sensitivity experiments. We found that the atmospheric forcing not only affects the SST modes on shorter time-scales directly, but also shows its influence on longer time scales via air-sea interaction, amplification and oceanic feedback. The deep mixed layer in the Southern Ocean is an essential element to maintain the long-term SST variability. The ocean dynamics connect the entire ocean and create the homogeneous-like spatial patterns. The ocean advection is the key factor to create SST spectral structure, which concentrates the spectrum on interannnual scale synchronizing with the transport of Antarctic Circumpolar Current (ACC).